Acute Safety of an Open-Irrigated Ablation Catheter with 56-Hole Porous Tip for Radiofrequency Ablation of Paroxysmal Atrial Fibrillation: Analysis from 2 Observational Registry Studies - OZA, SAUMIL R (J Cardiovasc Electrophysiol, 2014)
INTRODUCTION: This report presents safety data on the use of a new open-irrigation radiofrequency ablation (RFA) catheter with a 56-hole porous tip in 742 patients enrolled in 2 US prospective, multicenter observational registry studies representing real-world use of the catheter. METHODS: This analysis is comprised of patients who underwent RFA of drug-refractory recurrent symptomatic paroxysmal atrial fibrillation (AF). Acute adverse events (AEs) were collected and categorized by seriousness, timing, and relatedness, with 7 days of follow-up data in one study and at least 120 days of data from a 1-year follow-up in the other. Acute serious adverse events (SAEs) that were identified as potentially related to the device and/or procedure were adjudicated by an independent safety committee. RESULTS: A total of 30 patients (4.0%) in the combined studies experienced an acute SAE related to the device and/or procedure, which was similar in the subset of patients age 65 and over (4.2%). These SAEs included 1.2% cardiac tamponade/perforation, 0.7% pericarditis, 0.5% pulmonary events, and 0.8% vascular access complications. No myocardial infarction, stroke, transient ischemic attack, or atrioesophageal fistulas within 7 days postprocedure were reported. In the study with extended follow-up, 1 pulmonary vein stenosis and 1 esophageal injury were seen beyond 7 days postprocedure (0.2% each). There were no device or procedure related deaths. CONCLUSION: Results from 2 large observational studies demonstrated that a new porous tip RFA catheter was safe for the treatment of drug refractory, recurrent, symptomatic paroxysmal AF, including treatment of older patients (≥65 years).